Recognition of CD8+ T-cell epitopes to identify adults with pulmonary tuberculosis - Swarbrick, G. M.; Park, B.; Lancioni, C.; Nsereko, M. (Eur Respir J, 2019)
Tuberculosis (TB), the disease caused by Mycobacterium tuberculosis (Mtb), remains a leading cause of morbidity and mortality. Current tools to identify Mtb-infected individuals, specifically interferon-γ release assays (IGRAs) and the tuberculin skin test (TST), cannot distinguish between asymptomatic Mtb-infected individuals (latent Mtb infection (LTBI)) and those with TB [1]. Advancement of TB diagnostics and their application in TB-endemic settings requires an assay that distinguishes between individuals with LTBI and TB. In this pilot study, we compared the ability of three CD8+ T-cell-based assays to distinguish Ugandan adults with: confirmed pulmonary TB (HIV-uninfected and HIV-infected), LTBI (HIV-uninfected only), and those who are TST-negative (HIV-uninfected only).
Keywords: CD8+ T-cell epitopes; Adults; Pulmonary tuberculosis